Residual-Income-Based Valuation Predicts Future Stock Returns: Evidence on Mispricing vs. Risk Explanations - Ali, Ashiq; Hwang, Lee-Seok; Trombley, Mark A. (The Accounting Review, 2003)
Frankel and Lee (1998) show that the value-to-price ratio (Vf/P) predicts future abnormal returns for up to three years, where Vf is an estimate of fundamental value based on a residual income valuation framework operationalized using analyst earnings forecasts. In this study, we examine whether the Vf/P effect is due to market mispricing or omitted risk factors. We find that the Vf/P effect is partially concentrated around the future earnings announcements, consistent with the mispricing explanation. On using an extensive set of risk proxies, suggested by Gebhardt et al. (2001) and Gode and Mohanram (2001), we also find that Vf/P is significantly related to some risk proxies. However, after controlling for these risk factors, Vf/P continues to exhibit a significant positive association with future returns suggesting that these risk factors are not responsible for the Vf/P effect. Overall, the results seem consistent with the mispricing explanation for the Vf/P effect.